Ashamed and Fused with Body Image and Eating: Binge Eating as an Avoidance Strategy - Duarte, Cristiana (2017)
Binge Eating Disorder (BED) is currently recognized as a severe disorder associated with relevant psychiatric and physical comorbidity, and marked emotional distress. Shame is a specific negative emotion that has been highlighted as central in eating disorders. However, the effect of shame and underlying mechanisms on binge eating symptomatology severity remained unclear. This study examines the role of shame, depressive symptoms, weight and shape concerns and eating concerns, and body image-related cognitive fusion, on binge eating symptomatology severity. Participated in this study 73 patients with the diagnosis of BED, established through a clinical interview-Eating Disorder Examination 17.0D-who completed measures of external shame, body-image related cognitive fusion, depressive symptoms and binge eating symptomatology. Results revealed positive associations between binge eating severity and depressive symptoms, shame, weight and shape concerns, eating concerns and body image-related cognitive fusion. A path analysis showed that, when controlling for the effect of depressive symptoms, external shame has a direct effect on binge eating severity, and an indirect effect mediated by increased eating concern and higher levels of body image-related cognitive fusion. Results confirmed the plausibility of the model, which explained 43% of the severity of binge eating symptoms. The proposed model suggests that, in BED patients, perceiving that others see the self negatively may be associated with an entanglement with body image-related thoughts and concerns about eating, which may, in turn, fuel binge eating symptoms. Findings have important clinical implications supporting the relevance of addressing shame and associated processes in binge eating. Copyright © 2015 John Wiley & Sons, Ltd.